Avaliação do albedo em área agrícola no leste da Amazônia - Br-163 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The advance of agriculture in natural areas and even protected areas has been a problem, removing the natural vegetation cover in the region and impacting the local ecosystem. The northern region has expanded considerably in agricultural production, on the br-163 near Santarém the change in the natural cover of the region is already visible, giving way to the planting of rice, soy and other crops. Evaluate the albedo obtained by the SEBAL model, using data from the Landsat 5 Sensor TM, in an agricultural field on the Santarém – Cuiabá Highway (BR -163) km 77 in eastern Amazonia. In order to analyze the change in surface conditions and estimate the NDVI, surface temperature and albedo influence the shortwave radiation reflection process, justifying the impact of this change on the forest cover in the region. Methodology: Landsat 5 satellite multispectral images of the Sensor TM were used, free of charge, obtained on the website of the National Institute for Space Research (INPE), which will be used in the semi-empirical model SEBAL, developed by BASTIAANSEEN (1995), in which images are used multispectral data from satellites and little surface data, such as air temperature and humidity to obtain the Energy Balance components. The study area is located in the municipality of Belterra-PA, along the BR 163 and the micrometeorological tower located in the agricultural field (Fazenda Paraíso) located approximately 77 km from the city of Santarém - PA. In the albedo analysis, it was noticed that the highest values occurred in the early hours of the morning and late afternoon, due to the dependence of this variable on the solar zenith angle (Souza et al. 2010), where the daily albedo averaged 0.215, compared with the values modeled by SEBAL, the agreement was reasonable. The discussion about the advancement of large-scale agriculture in the Amazon region is becoming more persistent because in recent years there has been a great wave of clearing of natural cover to make room for agriculture. This agricultural expansion is influencing surface albedo which may influence the amount of energy storage for biological, biochemical and biophysical processes in Amazonian ecosystems.
Keywords: Albedo; SEBAL; sensoriamento remoto; CNPQ:: GEOCIÊNCIAS